Influência de parâmetros operacionais na macroestrutura e propriedades mecânicas de ligas do sistema AL-ZN solidificadas através do processo squeeze casting - Lima, Robson Andrade de (2014)
The process Squeeze casting is a casting process in which the cast metal is solidified in the liquid state under pressure into a metallic permanent mold closed by a puncture. It is an economical and relatively simple technique, possessing great potential for automation and high production rates. The product is of high quality and usually has the final form. Currently, components of aluminum alloys, copper, magnesium, cast iron, stainless steels and nickel-based superalloys are easily manufactured by squeeze casting, for our work alloy studied for this process was the Aluminum Alloy Zinc. The aim of this study was to analyze the influence of operating parameters such as pressure and pressing time on the correlation between solidification macrostructure and mechanical properties of dilute Al-Zn through the process Squeeze Casting, alloy alloys used in this work of Al-1% Zn ; Al-3% Zn and 5% Al-Zn, and pressures of 50, 100 and 150 MPa and solidification without pressure and with pressing time of 5 seconds. The results show the macrostructure, tensile test and hardness. The study of macro-structure and properties of these alloys shows the effectiveness of this process in the grain refining and improves the mechanical properties of the alloys studied.